An injectable multi-responsive hydrogel as self-healable and on-demand dissolution tissue adhesive. (March 2021) - A, Sigen; Xu, Qian; Johnson, Melissa; Creagh-Flynn, Jack; Venet, Manon; Zhou, Dezhong; Lara-Sáez, Irene; Tai, Hongyun; Wang, Wenxin
Highlights: A novel multi-responsive hyaluronic acid hydrogel system with self-healing property was fabricated by dynamic covalent chemistry. The hydrogel showed controlled degradation behaviours under external stimuli including shear force, reduction agent, oxidation agent, hyaluronidase, and UV irradiation. The optimized injectable hydrogel can be used for wound closure owing to the good biocompatibility, rapid gelation rate, on demand degradation profile, and high tissue adhesive strength. Abstract: The development of new tissue adhesives is still in great demand as the current available tissue adhesives cannot meet the requirements of sophisticated surgeries. One major limitation of current adhesives is difficult to balance the adhesive strength, the mechanical property and the responsive degradation rate. Herein, we report a new injectable and self-healable hydrogel, which can function as a multi-responsive tissue adhesive with on-demand degradation profile under different external stimuli. The adhesive hydrogel is composed of aldehyde functionalized hyaluronic acid (HA-CHO) and a disulfide containing crosslinker - 3, 3′-dithiobis(propionic hydrazide) (DTPH). With the optimized formulation, the gelation can be formed within 1 min in situ. Multi responsive properties were introduced into this adhesive hydrogel, namely (1) Strain-responsive; (2) Reduction-responsive; (3) Oxidation-responsive; (4) Enzyme-responsive; and (5) UV-responsive properties. Bovine serum albumin (BSA)/Glutaraldehyde hydrogel - a commercial tissue adhesive BioGlue Ⓡ, was selected as the control. Remarkably, this new hydrogel showed much high lap shear adhesive strength (up to 120 kPa) to the porcine skin, which surpasses 65.8% to BioGlue Ⓡ . Graphical abstract: An injectable and self-healing hydrogel with on-demand degradation profile was developed that can function as a multi-responsive tissue adhesive. The hydrogel was crosslinked by dynamic covalent bond and subtly designed to possesses five responsive properties. The hydrogel showed a significantly higher lap shear strength than BioGlue Ⓡ, a well-known commercial adhesive product. Image, graphical abstract